737 STOOLS FOR STOOLS - COMBINING MEDICAL AND CONSERVATIVE TREATMENTS TO REDUCE CONSTIPATION IN THE ELDERLY INPATIENT POPULATION. (8th March 2022) - Roth, N; Khalil, N; Moore-Gillon, C; James, D; Gilby, L; Morgan, C
Abstract: Introduction: Constipation is a common cause of morbidity in the elderly. Its management is particularly challenging in the inpatient population, where many factors exacerbate constipation. We describe a Quality Improvement Project to reduce the rates of constipation on a female Medicine for the Elderly ward. Aims: Our aim was to increase bowel chart documentation (nursing and doctor entries) and increase patient frequency of bowel motions to at least once every two days. In particular we focused on conservative measures such as the use of footstools to optimise posture when using commodes and toilets [R Hari Krishnan, Proc Inst Mech Eng H, 2019, 233(4):464–475]. Method: Weekly monitoring of ward inpatients. Measurements taken were: days since last bowel motion, laxatives prescribed, bowel chart and ward round documentation, and episodes of diarrhoea over the past week. One episode of diarrhoea was defined as 3 motions of type 6 or type 7 stool in 24 hours. A new intervention was introduced every two weeks, over a total of 2 months. Interventions: 1. Recording bowel motions at the daily 'Board Round' Multi-Disciplinary Meeting. 2. Ward staff education sessions. 3. Footstools for use with commodes and toilets. 4. High-fibre foods to patients with constipation. Results: Level of constipation was successfully reduced, with 100% patients moving bowels every 2 days from a baseline of 68%. Ward round and bowel chart documentation improved to 100% and 93.3% respectively (from 41.3% and 33.3%). However, incidence of diarrhoea increased from 0 episodes/week to 8 episodes/week, with laxative prescriptions similarly increased from 50% to 86%. Conclusion: Constipation improved with our interventions, but at the unintended cost of laxative-associated diarrhoea. Our next steps will be to reduce laxative prescriptions in favour of conservative measures, in order to reduce episodes of loose stool while maintaining our improved constipation rates.